Business Feasibility of Quail Probiotic:A Study in Bandung Vicinity, West Java, Indonesia - Sutisna, Deden; Siti Fauziyah Hasanah, Furi; Haizam Bin Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The increasing culinary trend in Bandung encourages businesses to continue to innovate. In addition to diversity, the nutritional value of food is the main requirement to survive in this industry. Probiotic quail livestock is a business with good prospects. This is because the demand for meat and agg quail tends to increase from year to year in line with the increasing population growth and the increasing number of people who are aware of healthy living. An Increase in demand for quail meat and egg needs, this can indicate that business opportunities in the field of quail breeding is still wide open, therefore it is necessary to analyze whether the business is feasible to do. This study examines the opportunities for probiotic quail business development based on entrepreneurial aspects of the Timmons model and aspects of business feasibility studies which consists of legal aspect, market and marketing aspects, financial aspects, technical and technological aspects, and management and human resources aspects. This business development plan starts based on the Payback Period criteria, Net Present Value, Profitability Index and Internal Rate of Return. The results of the study showed that the investment for the development of probiotic quail broiler businesses was Rp. 232.49 million, - using loans through banking and private capital. Positive NPV of Rp. 184.279188., IRR 57%, NPM 20.32%, and return on investment for 1 year 8 month 20 days. These results indicate that the development of probiotic broilers is feasible because it can provide benefits.